2009
DOI: 10.1080/09540120902803190
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of contextual factors that influence HIV risk in female sex workers in Mexico: The Social Ecological Model applied to HIV risk behaviors

Abstract: The present study examined the applicability of the Social Ecological Model for explaining condom use in a sample of female sex workers (FSWs) (N=435) participating in a behavioral intervention to increase condom use in Tijuana, Mexico. Using a multi-group path analysis, we compared women who work in bar settings (n=233) to those who worked on the street (n=202) with regard to an individual factor (self efficacy), an interpersonal factor (client financial incentives), and a structural factor (condom access). C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
2
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 36 publications
0
76
2
3
Order By: Relevance
“…information and communication technologies (Muturi, 2005;Van Donk, 2006), all of which are likely to lead to variations in HIV=AIDS-related outcomes. Health promotion programs have long recognized the importance of socioecological factors (McLeroy, Bibeau, Steckler, & Glanz, 1988) and have considered them vital to the design of prevention interventions including those that address HIV=AIDS (Larios et al, 2009). Given this, it is logical to anticipate urban-rural differences in attitudes, perceived norms, and self-efficacy beliefs related to HIV testing that might lead to variations in intention to be tested for the infection.…”
Section: Introductionmentioning
confidence: 99%
“…information and communication technologies (Muturi, 2005;Van Donk, 2006), all of which are likely to lead to variations in HIV=AIDS-related outcomes. Health promotion programs have long recognized the importance of socioecological factors (McLeroy, Bibeau, Steckler, & Glanz, 1988) and have considered them vital to the design of prevention interventions including those that address HIV=AIDS (Larios et al, 2009). Given this, it is logical to anticipate urban-rural differences in attitudes, perceived norms, and self-efficacy beliefs related to HIV testing that might lead to variations in intention to be tested for the infection.…”
Section: Introductionmentioning
confidence: 99%
“…In Tijuana, street-based workers are marginalized to a greater extent and are more likely to experience police harassment, exploitation, and abuse, placing them at increased risk for unsafe sex and increased drug activity. 9,10 The effect of geography on HIV/STI risk likely reflects macrolevel factors that hinder working in safer sex work environments. For example, one study concluded that Canadian FSWs spatially displaced to side streets experienced decreased access to preventive services and harm reduction resources.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 shows the baseline demographic, socioeconomic, and working conditions of the 410 FSWs. The median age was 32 (interquartile range [IQR]: [25][26][27][28][29][30][31][32][33][34][35][36][37][38], and most women were migrants to Baja California (78%). Less than one-fifth were married (19%).…”
Section: Resultsmentioning
confidence: 99%
“…The current registration system may be excluding sex workers who operate outside of a specific venue, and thus the MHD may not be reaching women at highest risk for HIV and STIs. Because street-based FSWs are more likely to be infected with HIV and STIs and to use drugs, 37 efforts are needed to reach out to these women, who may fear they will be denied registration if they test HIV-positive. Since our study was conducted, a mobile HIV-prevention campaign has been initiated in Tijuana, representing a partnership between a local nongovernmental organization and the municipal, state, and federal governments.…”
Section: Factors Independently Associated With Fsw Registrationmentioning
confidence: 99%